Analisis Perkembangan Usaha Mikro, Kecil dan Menengah (Umkm) Sebelum dan Sesudah Memperoleh Pembiayaan dari Lembaga Keuangan Syariah: (Studi Kasus UMKM Kabupaten Bandung) - Budi Rustandi Kartawinata; Candra Wijayangka; Hanansa R Dabinda; Salma Aprilia (Komunitas Dosen Indonesia, 2020)
This research was conducted to determine the development of Micro, Small and Medium Enterprises (MSMEs) before and after obtaining financing from syariah financial institutions (case study: MSMEs around the Dayeuhkolot market). This study uses a quantitative method with a type of descriptive-comparative research. Sampling is done by non-probability sampling method type of proporsive sampling, with the number of respondents as many as 30 people. The data analysis technique is used descriptive analysis. Based on the results of testing the hypothesis significantly, the development of MSMEs around the Dayeuhkolot market experienced significant differences before and after obtaining financing from syariah financial institutions. This is evidenced by z count ? z table, namely for the dimension of sales turnover is 4.794 ? 2.042, the dimension of labor is 4.673 ? 2.042, and the customer dimension is 4.766 ? 2.042 with a significance level of 0.000 <0.05. Conclusion of this study, the development of MSMEs on the dimensions of sales turnover fall into the very good category, in the dimensions of labor included in the category quite well, and on the dimensions of the customer included in the fairly good category. Keywords: development of MSMEs, sales turnover, labor, customers, financing